Osteomyelitis kronis supuratif mandibula sebagai komplikasi sekunder impaksi gigi molar tiga - Heinz Frick Simanjuntak; Melita Sylvyana; Fathurachman Fathurachman (MKGK (Majalah Kedokteran Gigi Klinik) (Clinical Dental Journal) UGM, 2016)
Chronic osteomyelitis suppurative the mandible as a complication secondary impaction of the mandibular third molars. Impacted third molars is a common thing and become a common reason patients seek dental treatment. Complications of impacted teeth is the most frequently occurring infection oromaksilofasial particularly acute infection. Suppurative osteomyelitis of the mandible due to secondary complications of impacted molars wisdom is rare. The aim of this case report describe treatment  of chronic suppurative osteomyelitis is caused secondary complications of impacted third molars. A female patient reported a history of recurrent toothache previous six months in the region of the right mandible and develop into extra-oral fistula since the last three months. Swelling that does not improve to make the patient come to the oral surgeon poly rs Hasan Sadikin. Preoperative panoramic radiographs showed mesioangular impacted third molars right mandible with deep caries and periapical radiolucent area of the mesial root of the tooth. From the results of clinical examination and radiographic findings made the diagnosis of chronic osteomyelitis of the mandible. Sequesterectomy and extraction of mandibular right second molar and all third molars upper and lower jaw. Sinus passages excised and closure. Histopathological examination conducted on tissues resected. Sekuesterektomi, fistulektomi and causa tooth extraction is a definitive method for treating chronic osteomyelitis with a satisfactory clinical outcome after surgery